An embodiment paradigm in evaluation of human-in-the-loop control. Issue 34 (2019) - Fröhner, Jakob; Beckerle, Philipp; Endo, Satoshi; Hirche, Sandra
Abstract: This study introduces a novel approach for evaluating the quality of human-in-the-loop control using the psychological construct of embodiment in a haptic human-machine interaction task. Despite the fact that various forms of assistive control have been introduced, these methods mainly design semi-autonomous control to improve task-specific interaction performance. From a user perspective, however, the introduction of semi-autonomous control reduces controllability of the system, which could lead to negative user experience. Psychological research suggests sensory-motor factors dynamically modulate cognition of an external entity belonging to one's own body, i.e., embodiment. In our paradigm, we apply methods for evaluating embodiment in a virtual reality (VR) environment where the human users perform a reaching task with semi-autonomous haptic assistance to measure the degree to which the embodiment is effected by the quality of semi-autonomy Our results with 8 participants show good persistence of subjective embodiment and subcomponents of presence within VR environment when a predictable assistive control is introduced while unpredictable assistance hindered the subjective embodiment. Results indicate embodiment can be exploited as a quantitative evaluation method of semi-autonomous controllers from a user-centric perspective.